HUBUNGAN PERANAN ORANG TUA DENGAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII SELAMA PEMBELAJARAN ONLINE DI SMP NEGERI 6 KOTA JAMBI - Hikmah, Indah Hijratul; Harman, Harman; Dewi, Sri (Universitas Batanghari Jambi, 2021)
This research is a quantitative study that uses correlation coefficient analysis which aims todetermine the significant relationship between the role of parents (X) and mathematics learning outcomes (Y). The population in this study were all eighth grade students of SMP Negeri 6 Jambi City for the 2020/2021 academic year with a total of 393 students divided into 11 classes. The sample in this study amounted to 99 students divided into 11 classes taken by random sampling (random technique). The research instrument used was a questionnaire and a test of learning outcomes in the form of a description. The results of the descriptive analysis obtained a description of the role of parents of students in general are included in the medium category with a percentage of 65.7%, the lowest score is 70, the highest is 122, the range is 52 and an overview of students' mathematics learning outcomes in general is included in the medium category with a percentage of 65.7%. , the lowest score was 20, the highest score was 93 and the range was 73. From the inferential analysis, there is a significant relationship between the role of parents and students' mathematics learning outcomes during online learning for class VIII SMP Negeri 6 Jambi City. This can be seen from the results of the correlation coefficient test analysis, the value of r = 0.654, which means that the relationship between the role of parents and students' mathematics learning outcomes is in a strong relationship, then an r2 value of 0.427 indicates that the role of parents contributes to learning outcomes. mathematics by 42.7% of the significant test obtained a value of 0.000 where the value of sig <0.05 then H0 is rejected. So it can be concluded that there is a significant relationship between the role of parents and the mathematics learning outcomes of seventh grade students of SMP Negeri 6 Jambi City.